KEBIJAKAN DESENTRALISASI PENDIDIKAN: ANALISIS PERBANDINGAN IMPLEMENTASI STRATEGI PEMBELAJARAN DI SAUDI ARABIA DAN INDONESIA - Ika Kurnia Sofiani; Ahmad Madany; Muhammad Iqbal (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study examines the policy of educational decentralization through a comparative analysis of the implementation of instructional strategies in Saudi Arabia and Indonesia. The study aims to evaluate the extent to which this policy contributes to the effectiveness of instructional strategies and to identify its strengths and challenges in both countries. The findings reveal that decentralization allows educational institutions to innovate and adopt more contextual and participatory teaching approaches. However, issues such as disparities in resources, institutional capacity, and policy consistency across regions pose significant challenges. The study recommends strengthening local capacities, enhancing coordination among stakeholders, and integrating national and local policies to promote equity and improve the quality of education under a decentralized system.